Age-adjusted D-dimer thresholds in the investigation of suspected pulmonary embolism: A retrospective evaluation in patients ages 50 and older using administrative data. Issue 5 (5th June 2018) - Senior, Kevin; Burles, Kristin; Wang, Dongmei; Grigat, Daniel; Innes, Grant D.; Andruchow, James E.; Lang, Eddy S.; McRae, Andrew D.
Abstract : CLINICIAN'S CAPSULE : What is known about the topic? Age-adjusted D-dimer thresholds have been proposed to improve specificity of diagnostic testing for thromboembolism in patients ages 50 and over. What did this study ask? What is the diagnostic accuracy of an age-adjusted D-dimer threshold in a population of patients undergoing investigations for suspected pulmonary embolism (PE)? What did this study find? Age-adjusted D-dimer cut-offs improved specificity but at the expense of a slightly higher risk of missed PE. Why does this study matter to clinicians? Use of age adjusted D-dimer thresholds, in combination with validated risk scores, may reduce CT utilization in older patients. Abstract: Objectives: D-dimer testing is an important component of the workup for pulmonary embolism (PE). However, age-related increases in D-dimer concentrations result in false positives in older adults, leading to potentially unnecessary imaging utilization. The objective of this study was to quantify the test characteristics of an age-adjusted D-dimer cut-off for ruling out PE in older patients investigated in actual clinical practice. Methods: This observational study used administrative data from four emergency departments from July 2013 to January 2015. Eligible patients were ages 50 and older with symptoms of PE who underwent D-dimer testing. The primary outcome was 30-day diagnosis of PE, confirmed by imaging reports. Test characteristics of the D-dimer assay were calculated using the standard reference value (500 ng/ml), the local reference value (470 ng/ml), and an age-adjusted threshold (10 ng/ml × patient's age). Results: This cohort includes 6, 655 patients ages 50 and older undergoing D-dimer testing for a possible PE. Of these, 246 (3.7%) were diagnosed with PE. Age-adjusted D-dimer cut-offs were more specific than standard cut-offs (75.4% v. 63.8%) but less sensitive (90.3% v. 97.2%). The false-negative risk in this population was 0.49% using age-adjusted D-dimer cut-offs compared with 0.15% with traditional cut-offs. Conclusion: Age-adjusted D-dimer cut-offs are substantially more specific than traditional cut-offs and may reduce CT utilization among older patients with suspected PE. We observed a loss of sensitivity, with an increased risk of false-negatives, using age-adjusted cut-offs. We encourage further evaluation of the safety and accuracy of age-adjusted D-dimer cut-offs in actual clinical practice. RÉSUMÉ: Objectif: Le dosage des D-dimères est un élément important du bilan exploratoire de l'embolie pulmonaire (EP). Toutefois, l'augmentation du taux de D-dimères liée à l'âge se traduit par des faux positifs chez les personnes âgées ou d'âge mûr, ce qui peut conduire au recours inutile aux examens par imagerie. L'étude décrite ici visait donc à quantifier les caractéristiques de l'analyse en vue de la détermination d'un seuil de D-dimères rajusté selon l'âge qui permettrait d'écarter la présence d'une EP chez les personnes âgées ou d'âge mûr examinées en pratique clinique. Méthode: Il s'agit d'une étude d'observation, réalisée à l'aide de données administratives, dans quatre services des urgences, de juillet 2013 à janvier 2015. Les patients admissibles étaient des personnes de 50 ans et plus, qui présentaient des symptômes d'EP et qui ont été soumises au dosage des D-dimères. Le critère d'évaluation principal consistait en la pose du diagnostic d'EP au bout de 30 jours, confirmé par des examens d'imagerie. Les caractéristiques de l'analyse en vue du dosage des D-dimères étaient calculées à l'aide de la valeur de référence usuelle (500 ng/ml), de la valeur de référence locale (470 ng/ml) et du seuil rajusté selon l'âge (10 ng/ml x l'âge du patient). Résultats: La cohorte comptait 6655 patients, âgés de 50 ans et plus, qui avaient été soumis au dosage des D-dimères en raison d'une possible EP. Un diagnostic d'EP a été posé chez 246 d'entre eux (3, 7 %). Les seuils de dosage des D-dimères rajusté selon l'âge étaient plus spécifiques (75, 4 % contre 63, 8 %) mais moins sensibles (90, 3 % contre 97, 2 %) que les seuils usuels. Le risque de faux négatifs, dans la population sélectionnée, s'est établi à 0, 49 % à l'aide des seuils de D-dimères rajustés selon l'âge comparativement à 0, 15 % pour les seuils habituels. Conclusion: Les seuils de D-dimères rajustés selon l'âge sont beaucoup plus spécifiques que les seuils usuels, d'où une réduction possible du recours à la tomodensitométrie parmi les personnes âgées ou d'âge mûr chez qui l'on soupçonne la présence d'une EP. Toutefois, une perte de sensibilité du dosage, accompagnée d'une augmentation du risque de faux négatifs, a été observée avec l'utilisation des seuils rajustés selon l'âge. Il serait donc justifié d'approfondir l'innocuité et l'exactitude des seuils de D-dimères rajustés selon l'âge en pratique clinique.